2014
DOI: 10.15835/buasvmcn-asb:10586
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Nitrogen Dynamics in an Integrated Stellate Sturgeon and Spinach Aquaponic System with Different Crop Densities

Abstract: Obtaining and maintaining a healthy, productive aquaponic system requires intensive scienti ic research, monitoring and also adjustments, when necessary. To quantify the nitrogen budget for a stellate sturgeon-spinach integrated LECA grow bed aquaponic system, where three plants densities were used. The experiment was made in triplicate, using a 12 aquaponic units LECA grow bed aquaponic system. Three crops densities were used (V1-59crops/m 2 , V2-48crops/m 2 and V3-39crops/m 2 and V4-no crops, only with LECA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The study conducted by Petrea et al in 2013 concluded that the nitrite and nitrate content of spinach could be affected by plant density, and they also stated that spinach-trout aquaponics met food safety requirement (Petrea et al, 2013). Some studies focused on the hydraulic loading rate and plant ratio (Endut et al, 2010); while others focused on calcium and phosphorous dynamic (Petrea et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Petrea et al in 2013 concluded that the nitrite and nitrate content of spinach could be affected by plant density, and they also stated that spinach-trout aquaponics met food safety requirement (Petrea et al, 2013). Some studies focused on the hydraulic loading rate and plant ratio (Endut et al, 2010); while others focused on calcium and phosphorous dynamic (Petrea et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Petrea et al in 2013 concluded that the nitrite and nitrate content of spinach could be affected by plant density, and they also stated that spinach-trout aquaponics met food safety requirement (Petrea et al, 2013). Some studies focused on the hydraulic loading rate and plant ratio (Endut et al, 2010); while others focused on calcium and phosphorous dynamic (Petrea et al, 2014). A study conducted by Liang and Chien in 2013 suggested that increasing feeding frequency and extending photo period would increase fish and plant yield, and decrease water nitrogen and phosphorus accumulation ( Liang and Chien, 2013).…”
mentioning
confidence: 99%
“…No LCA or TEA has been conducted to DDGS fractionation. There are some researches (Bailey et al, 1997;Rokacy, 2004;Villarroel et al, 2011;Petrea et al, 2013;Bunyaviroch et al, 2013;Sace and Fitzsimmons, 2013; Love et al, 2014; 2015) on aquaponics, including nutrient cycle and economic cost and profit of various aquaponics systems, but no complete LCA and TEA has been conducted to aquaponics located on mainland of U.S., which indicates there are some data gaps to explore more in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researches mainly focused on how to optimize aquaponics operation. The study conducted by Petrea et al in 2013 concluded that the nitrite and nitrate content of spinach could be affected by plant density, and they also stated that spinach-trout aquaponics met food safety requirement (Petrea et al, 2013). Some studies focused on the hydraulic loading rate and plant ratio (Endut et al, 2010); while others focused on calcium and phosphorous dynamic (Petrea et al, 2014).…”
Section: Aquaponicsmentioning
confidence: 99%
See 1 more Smart Citation